PENDAMPINGAN PENGENALAN WAYANG KULIT DALAM PENANAMAN SPIRITUALISME MELALUI CERITA DEWARUCI BAGI ANAK MIGRAN DI MALAYSIA - Dodi Kurniawan; Yasin Nur falah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service activity focuses on the lack of understanding of spiritual values ​​among Indonesian migrant children in Malaysia, despite their demonstrated interest in traditional arts. The objective of the activity is to instill spiritual awareness through a local cultural approach, specifically the shadow puppet play Dewa Ruci, which is steeped in Sufism (takhalli, tahalli, tajalli) and symbolizes human duality. The method used is Participatory Action Research (PAR) with five stages: to know, to understand, to plan, to act, and to change. The activity was carried out at the Sungai Mulia 5 Guidance Center (SBSM 5) in Gombak. The results showed an increased interest in culture, understanding of spiritual values, and deeper self-reflection. Shadow puppetry has proven to be an effective educational medium in non-formal education, supporting the sustainable development of character, spiritual awareness, and cultural identity in migrant children.